2013
DOI: 10.1155/2013/724378
|View full text |Cite
|
Sign up to set email alerts
|

Single Channel Speech Enhancement Using Adaptive Soft-Thresholding with Bivariate EMD

Abstract: This paper presents a novel data adaptive thresholding approach to single channel speech enhancement. The noisy speech signal and fractional Gaussian noise (fGn) are combined to produce the complex signal. The fGn is generated using the noise variance roughly estimated from the noisy speech signal. Bivariate empirical mode decomposition (bEMD) is employed to decompose the complex signal into a finite number of complex-valued intrinsic mode functions (IMFs). The real and imaginary parts of the IMFs represent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Several approaches are developed in earlier based on EMD [6]. In [6], an adaptive soft thresholding algorithm was developed based on EMD.…”
Section: Intrinsic Mode Functions (Imfs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches are developed in earlier based on EMD [6]. In [6], an adaptive soft thresholding algorithm was developed based on EMD.…”
Section: Intrinsic Mode Functions (Imfs)mentioning
confidence: 99%
“…In [6], an adaptive soft thresholding algorithm was developed based on EMD. Here the variance is derived for every IMF not for speech signal by which this algorithm achieved better performance.…”
Section: Intrinsic Mode Functions (Imfs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression to calculate the optimum adaptation factor (λ opt ) is defined as (19) to fit the data points (v i , w i ), i=1,2,….., d(=9); where v i and w i are the input SNR and optimum value of λ (to obtain the maximum output SNR) respectively as listed in Table 2. We experimentally found that there is a nonlinear relation between the input SNR and adaptation factor, for that we choose a third degree polynomial to fit the non-linear data points with minimum stable coefficients [40]. To obtain the coefficients, Eq.…”
Section: Adaptive Soft-thresholding (Asth)mentioning
confidence: 99%
“…Such method degrades the performance of speech enhancement when the speechless is not detected perfectly. Bivariate EMD (bEMD) based approach is implemented for effective noise estimation to derive the parameters required for soft-thresholding [41]. In bEMD, two variables are decomposed simultaneously without losing mutual dependency.…”
Section: Adaptive Soft-thresholding (Asth)mentioning
confidence: 99%